An Evaluation of the Mechanisms of Galacto-Oligosaccharide (GOS)-Induced IgE Cross-Linking on Basophils in GOS Allergy - Lee, Li Yuan Gabriella Nadine; Leow, Si Yuan; Wen, Hongmei; Soh, Jian Yi; Chiang, Wen Chin; Zhong, Youjia; Tham, Elizabeth Huiwen; Loh, Wenyin; Delsing, Dianne J.; Lee, Bee Wah; Huang, Chiung-Hui (Frontiers in Allergy, 2022)
The prebiotics, galacto-oligosaccharides (GOS), are small carbohydrate molecules with 1–7 galactose units linked to glucose and have been shown to trigger IgE-mediated anaphylaxis in some cases following ingestion. It is still an unresolved question of how GOS cross-links IgE on basophils. In this study, we examined whether human galectins, a class of lectins that bind specifically to β-galactoside carbohydrates, are involved in GOS-induced basophil activation. Basophil activation test to GOS and control allergen, Blomia tropicalis (Blo t) extract were performed in the presence or absence of four sugar-based galectin inhibitors (lactose, thiodigalactoside [TDG], TD139, and GB1107) and one peptide-based inhibitor, G3-C12. Results showed that TD139, GB1107, and G3-C12 did not display a specific inhibitory effect on GOS-induced basophil activation as compared to control allergen. An inhibitory effect of lactose and TDG on GOS-induced basophil activation was observed and varied between subjects with up to 100% inhibition at low doses of GOS. The results of competitive ELISA suggest that the inhibitory effects of high dose lactose and TDG on the basophil activation is likely due to the cross-reactivity of GOS-specific IgE to lactose and TDG. Basophil activation is performed using purified basophils suggested that cell surface receptors on other blood cells were not required to induce basophil activation. In conclusion, our results suggest that GOS, a low molecular weight sugar, is able to cross-link IgE independently.